Amplification of Earthquake Ground Motions in Washington, DC, and Implications for Hazard Assessments in Central and Eastern North America. Issue 24 (23rd December 2017) - Pratt, Thomas L.; Horton, J. Wright; Muñoz, Jessica; Hough, Susan E.; Chapman, Martin C.; Olgun, C. Guney
Abstract: The extent of damage in Washington, DC, from the 2011 M w 5.8 Mineral, VA, earthquake was surprising for an epicenter 130 km away; U.S. Geological Survey "Did‐You‐Feel‐It" reports suggest that Atlantic Coastal Plain and other unconsolidated sediments amplified ground motions in the city. We measure this amplification relative to bedrock sites using earthquake signals recorded on a temporary seismometer array. The spectral ratios show strong amplification in the 0.7 to 4 Hz frequency range for sites on sediments. This range overlaps with resonant frequencies of buildings in the city as inferred from their heights, suggesting amplification at frequencies to which many buildings are vulnerable to damage. Our results emphasize that local amplification can raise moderate ground motions to damaging levels in stable continental regions, where low attenuation extends shaking levels over wide areas and unconsolidated deposits on crystalline metamorphic or igneous bedrock can result in strong contrasts in near‐surface material properties. Plain Language Summary: Shaking during earthquakes in geologically older continental regions like central and eastern North America extends for much greater distances than in younger regions like much of western North America. We show that amplification of ground motions by shallow layers of sediment beneath Washington, DC, likely was responsible for amplifying moderate ground motions during the Mw 5.8 Virginia earthquake in 2011 to damaging levels, despite the earthquake being relatively distant and only moderate in size. This study thus emphasizes the importance of local amplification effects in causing damage to cities in stable continental regions, where there can be strong contrasts in material properties between shallow sediments and underlying igneous or metamorphic bedrock. Key Points: Recordings from a temporary seismometer array document amplifications of earthquake ground motions in Washington, DC Damage in Washington, DC, during the 2011 M w 5.8 Mineral, VA, earthquake was likely increased by these locally amplified ground motions Amplification of ground motions in other central and eastern North American cities could raise ground motions from moderate earthquakes to damaging levels